2020
DOI: 10.1186/s10086-020-01875-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the mechanical performance of plywood used in membrane-type LNG carrier insulation systems

Abstract: In this study, the mechanical performance of melamine-urea-formaldehyde (MUF) resin plywood composed of an orthotropic material, which is used as a structural material in liquefied natural gas (LNG) cargo containment systems (CCSs), is evaluated. With a decrease in temperature, the plywood changes from ductile to brittle under compressive loads; thus, it may fail to distribute the compressive loads caused by sloshing impact as well as lose its stiffness, which helps maintain the shape of the structure. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…As a result of cooling from +40 to -40 °C, the BS and MOE values increased by 34 % and 38 %, respectively. Cha et al (2020) found that the MOE of plywood increased with decreasing temperature. Zhao et al (2015) studied the MOE of water-saturated, fresh-cut, air-dried, and oven-dried birch (Betula platyphylla) wood under the temperatures at +20 °C and -196 °C.…”
Section: Effect Of Freezing On the Mechanical Properties Of Plywoodmentioning
confidence: 97%
See 2 more Smart Citations
“…As a result of cooling from +40 to -40 °C, the BS and MOE values increased by 34 % and 38 %, respectively. Cha et al (2020) found that the MOE of plywood increased with decreasing temperature. Zhao et al (2015) studied the MOE of water-saturated, fresh-cut, air-dried, and oven-dried birch (Betula platyphylla) wood under the temperatures at +20 °C and -196 °C.…”
Section: Effect Of Freezing On the Mechanical Properties Of Plywoodmentioning
confidence: 97%
“…Mechanical properties such as bending strength (Kim et al 2015, Kim et al 2018, modulus of elasticity (Kim et al 2015, Kim et al 2018, tensile strength (Kim et al 2015) and compression strength (Cha et al 2020) have been found to increase during freezing in plywood made of the MUF and PF resins. Similarly, it has been discovered that compression strength and bending strength values increased in wood composites with decreasing temperatures (Ayrilmis et al 2010, Bekhta andMarutzky 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation